PENGARUH KEBIJAKAN DIVIDEN, PROFITABILITAS, STRUKTUR AKTIVA, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2014-2018) - Yang, Vania Florentina Santoso; Sri Sudarsi; Cahyani Nuswandari (Faculty of Economic and Business Universitas STIKUBANK, 2021)
Corporate financial management is one of the most important activity in keeping the sustainability of the corporate. Corporate prefers using internal financial sources, retained earnings, rather than external financial sources. However, if the internal financial sources cannot meet operating cost, then an alternative option of external financial sources is debt, and the last alternative is issuing new shares. This research aims to examine and analyze the effect of dividend policy, profitability, assets structure, and corporate size on corporate debt policy. This research uses financial report of manufacturing companies listed in Indonesian Stock Exchange in 2014 – 2018 as observation data. Sampling method used is purposive sampling method. The analytical method used in this research is multiple regression analysis, analyze using application SPSS version 21. The results of this study prove that corporate size has a positive and significant effect toward corporate debt policy, meanwhile dividend policy, profitability, and assets structure do not have effect toward corporate debt policy. The value of Adjusted R2 is 0.452, it shows that independent variables are able to explain dependent variable as much as 45.2% and the remaining 54.8% explained by other variables outside the model. Key words : dividend policy, profitability, assets structure, corporate size, and debt policy